Castable taking modified ball pitch as carbon source and used for blast furnace tapping channel and preparation method of castable
By using modified ball asphalt as a carbon source in the castable for blast furnace discharge grooves and optimizing the baking curve, the problems of the carbon source in the existing castable are not wet with water, weak oxidation resistance and poor slag corrosion resistance in the existing castable are solved, and higher oxidation resistance, mechanical properties and slag corrosion resistance are achieved, extending service life and reducing costs.
Patent Information
- Application Number
- CN202510048591.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-13
AI Technical Summary
During the use of the existing Al2O3-SiC-C castable for blast furnace discharge grooves, there are problems such as the carbon source not wet with water, weak oxidation resistance and poor slag corrosion resistance.
Modified ball asphalt is used as a carbon source and the baking curve of the castable is optimized. By loading nanosilicon dioxide on the surface of the ball asphalt, the hydrophilicity and dispersion of the ball asphalt are improved, and the formation of silicon carbide whiskers is promoted, thereby improving the slag corrosion resistance and oxidation resistance of the castable.
It effectively improves the oxidation resistance, mechanical properties and slag corrosion resistance of the castable material, extends the service life of the blast furnace iron groove, and reduces production costs.
Smart Images

Figure CN119797898A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory castables, and more specifically to a castable for a blast furnace tapping channel using modified spherical pitch as a carbon source and a preparation method thereof. Background Art
[0002] With the increase in the size of blast furnaces and the intensity of smelting, the amount of iron produced by blast furnaces has continued to increase, and the load on the blast furnace trough has increased. It is urgent to improve the comprehensive service performance of the trough castable to extend its service life. Carbon materials have poor wettability with molten slag and high thermal conductivity, which can improve the slag erosion resistance and thermal shock resistance of the trough castable and extend the service life of the blast furnace trough. At present, the carbon source used for Al2O3-SiC-C trough castables in industrial production is generally spherical asphalt.
[0003] Although ball asphalt has many advantages over traditional liquid or block asphalt, such as spherical shape and high fluidity, the following problems still exist in the actual use of Al2O3-SiC-C iron ditch castables: (1) During the pouring process, the carbon source is not wetted by water and is prone to agglomeration, which reduces the slag erosion resistance during the final use; (2) The residual carbon rate of ball asphalt is low and it is easily oxidized during use, which greatly reduces its service life and affects normal production efficiency; (3) At present, there is a lack of a clear baking system for Al2O3-SiC-C castables with ball asphalt as the carbon source, and there is no sufficient theoretical guidance, so the final use performance of the castable cannot be effectively guaranteed.
[0004] At present, there are many studies devoted to improving the comprehensive performance of Al2O3-SiC-C iron-outlet castables, among which the modification of carbon source is one of the important research directions. For example, the Chinese patent application with publication number CN113666723A discloses a carbon nanofiber-modified carbon-containing refractory castable and its preparation method. According to the weight percentage, the refractory castable includes: 100 parts of aggregate, 10 to 30 parts of binder, 8 to 15 parts of admixture and 0.2 to 0.8 parts of accelerator; wherein the aggregate is obtained by mixing refractory material and refractory coating liquid and sintering; the refractory coating liquid is a phenolic resin solution modified by ammonium cerium nitrate. The application uses the modified phenolic resin solution to coat the metal oxides conventionally used in the aggregate component of the refractory castable, and then sintering, and finally obtains the carbon nanofiber-modified carbon-containing refractory castable, which can effectively improve the slag erosion resistance of the castable. However, the preparation process of this application is relatively complicated, the preparation cost is high, it is not easy to realize industrial application, and there is still a lack of a clear baking system.
[0005] In addition, although the Chinese patent application with publication number CN106198301A discloses a method and device for formulating a baking system for refractory castables, specifically: using a temperature control system and a weighing system to monitor the temperature and weight changes of the castables, and analyzing the relationship between the weight and the temperature to obtain the water removal rate at different temperature stages, accurately obtain the baking effect of different castables at each temperature stage, determine the baking temperature and the baking time at the corresponding stage, and formulate the best baking system for the castables. However, the baking system in this application is formulated based only on the water removal rate at different temperature stages, which is not suitable for castables containing spherical asphalt with complex medium and low temperature thermal behavior, and its specific heating and baking stage is time-consuming and the heating curve is complex. Summary of the invention
[0006] 1. Technical problems to be solved
[0007] Aiming at the technical problems that the existing Al2O3-SiC-C castable for blast furnace tapping channel has defects such as carbon source not being wetted with water, weak oxidation resistance and poor slag erosion resistance during use, the present invention provides a castable for blast furnace tapping channel using modified spherical pitch as carbon source and a preparation method thereof. The scheme adopts modified spherical pitch as carbon source and optimizes the baking curve of the castable, so as to effectively improve the oxidation resistance and mechanical properties of the castable, as well as the synergistic fluidity and microcrystallization of the carbon source, and can promote the formation of silicon carbide whiskers, thereby improving the slag erosion resistance of the castable.
[0008] 2. Technical solution
[0009] In order to achieve the above object, the technical solution provided by the present invention is:
[0010] The first aspect of the present invention provides a castable for a blast furnace tapping channel using modified spherical asphalt as a carbon source. The castable raw material is Al2O3-SiC-C castable, which contains 2.3-5wt.% of modified spherical asphalt; the modified spherical asphalt is spherical asphalt with nano-silicon dioxide loaded on the surface.
[0011] Aiming at the technical problems existing in the existing Al2O3-SiC-C castables, the present invention improves the anti-iron corrosion performance of the castable by modifying the ball pitch. Specifically, the present invention can improve the hydrophilicity of the ball pitch by using nano-silicon dioxide and improve the dispersibility of the ball pitch in the castable matrix by coating the outer surface of the ball pitch with nano-silicon dioxide.
[0012] In addition, and more importantly, compared with nanocarbon and fine graphite, spherical pitch is solid shaped carbon and has no fluidity when baked at low temperature; while spherical pitch contains amorphous carbon with complex thermal behavior and has fluidity when baked at low temperature; therefore, the thermal behavior of spherical pitch in the casting baking process is essentially different from that of nanocarbon and fine graphite in the casting baking process. Because spherical pitch has more complex low-temperature thermal behavior, it has become a carbon source for castings for industrial applications. Specifically, spherical pitch softens and becomes a fluid colloidal state after heating. Therefore, when the casting is subsequently baked, on the one hand, the high expansion coefficient of air and the low viscosity of spherical pitch are combined, so that the spherical pitch expands rapidly when heated, and the spherical pitch penetrates, volatilizes and condenses into the pores inside the casting, thereby improving the density of the material and improving the overall performance of the casting. On the other hand, as the ball pitch flows in the castable matrix, the nano silicon dioxide attached to its surface can be evenly dispersed on the surface of the ball pitch, and evenly dispersed in the castable matrix along with the ball pitch, and the evenly dispersed nano silicon dioxide can play a better nucleation and filling effect. Specifically, the ball pitch will be microcrystallized into graphite during the baking process. In the subsequent use process, the graphite reacts with the nano silicon dioxide on its surface and the silicon powder in the matrix to generate a large number of spider web-like silicon carbide whiskers, which can more effectively connect the aggregate and powder in the matrix and fill the pores, further improving the densification degree of the castable, and further reducing the oxygen partial pressure inside the material, thereby improving the oxidation resistance of the castable. In addition, during the use of the castable, due to the uniform distribution of the carbon source in the castable and the silicon carbide whiskers hindering the further penetration of the slag, the anti-iron erosion performance of the castable has been greatly optimized. At the same time, the generated silicon carbide whiskers form granular silicon dioxide on its surface, filling the pores and further preventing oxygen from penetrating into the matrix. At the same time, they can also react with the aluminum-rich matrix to generate more evenly distributed mullite phases, which can effectively improve the bonding between the ball pitch and the aluminum-rich matrix, making its contact with the aluminum-rich matrix closer, and improving the densification of the sample, thereby further improving the overall high-temperature mechanical properties of the sample.
[0013] Furthermore, the particle size of the ball asphalt is 0 to 1 mm.
[0014] Furthermore, the castable raw materials also include 50-60wt.% brown corundum aggregate, 15-23wt.% silicon carbide, 11-38wt.% dense corundum compounded with α-alumina micropowder, 4-6wt.% calcium aluminate cement, and 1.5-2.0wt.% metallic aluminum powder compounded with elemental silicon powder.
[0015] Furthermore, the particle grading of the brown corundum aggregate is: 5-8 mm accounts for 25-45 wt.% of the brown corundum aggregate, 3-5 mm accounts for 15-35 wt.% of the brown corundum aggregate, 1-3 mm accounts for 15-30 wt.% of the brown corundum aggregate, and 0.088-1 mm accounts for 10-25 wt.% of the brown corundum aggregate.
[0016] Furthermore, the particle size composition of the silicon carbide is as follows: particles of 0.088 to 1 mm account for 40 to 55 wt.% of the silicon carbide, and particles smaller than 0.088 mm account for 45 to 60 wt.% of the silicon carbide.
[0017] Furthermore, the mass ratio of dense corundum to α-alumina micropowder in the dense corundum composite α-alumina micropowder is 0.1-0.2, and the particle size of the dense corundum is less than 0.045 mm; the α-alumina micropowder is selected from α-alumina micropowder with an Al2O3 content of ≥98wt.%, and a particle size distribution curve with a bimodal structure, and the bimodal peak values are 1.2μm and 2.3μm respectively.
[0018] Furthermore, the mass ratio of the metal aluminum powder to the elemental silicon powder in the metal aluminum powder compounded with the elemental silicon powder is 0.1 to 0.2.
[0019] Furthermore, the calcium aluminate cement is Secar71 pure calcium aluminate cement.
[0020] Furthermore, the water reducer is one or more of sodium tripolyphosphate, sodium hexametaphosphate, and polycarboxylic acid water reducer imported from BASF of Germany.
[0021] The second aspect of the present invention provides a method for preparing a high-performance blast furnace tapping ditch castable using the modified spherical pitch as a carbon source, including a baking process, wherein the baking process includes: keeping the castable at 330-370°C for 2.5-4h.
[0022] It should be noted that the present invention optimizes the baking process, and it is very important to keep the castable at 330-370°C for 2.5-4h. Through in-depth research on the complex thermal behavior of ball pitch, the inventor found that within a certain temperature range, as the baking temperature increases, its flow dispersion increases accordingly, but when the temperature exceeds a certain value, its flow dispersion begins to decrease. At the same time, the XRD spectrum of the ball pitch at the corresponding baking temperature is detected. The study found that with the increase of the baking temperature, the diffraction peak at 26° (2θ) becomes higher and sharper, indicating that the organic matter in the ball pitch evaporates, and the microcrystallization degree of carbon in the ball pitch is further improved. The increase in the degree of microcrystallization indicates that there are more carbon sources in the ball pitch that are converted from amorphous carbon to shaped carbon and lose fluidity. Therefore, within a certain temperature range, as the baking temperature increases, the fluidity of the ball pitch increases, but the microcrystallization of the ball pitch is also increasing.
[0023] According to the existence form of water in the castable, if only three common temperature points of 150℃, 550℃ and 800℃ are kept warm, the evaporation rate of different forms of water in the evaporating castable can be controlled. If the baking temperature is not properly selected, that is, according to the existing common heating rate of 15-25℃ / h, the temperature is directly increased from 150℃ to 550℃, then the residence time in the temperature range of the best balance between fluidity and microcrystallization is short, and the temperature range of the best balance between fluidity and microcrystallization is quickly crossed, and then microcrystallization is mainly used, resulting in poor fluidity dispersion of ball asphalt. The inventor is committed to finding the best balance between fluidity and microcrystallization of ball asphalt in castables, and finally determined that keeping warm at 330-370℃ for 2.5-4h can achieve the best balance between fluidity and microcrystallization of ball asphalt in the castable matrix. Keeping warm at this temperature can allow the modified ball asphalt to achieve the best flow expansion in the castable. The temperature is continued to rise at 330-370°C to bake the castable, after which the microcrystallization of the ball pitch is mainly carried out.
[0024] It should be noted that the best flow expansion of the ball pitch in the castable matrix is achieved by keeping the temperature within the range of 330-370°C for a period of time. On this basis, the dispersibility of the nano-silicon dioxide attached to its surface in the castable matrix and the ball pitch surface is further improved, so that the nano-silicon dioxide can play a better nucleation and filling effect.
[0025] Furthermore, regarding the selection of the insulation time, during the baking process of the castable, the insulation time in the temperature range of 330-370°C is selected to be 2.5-4h. If the insulation is too short, it will be detrimental to the flow and dispersion of the ball asphalt in the matrix. When the insulation time is greater than 4h, the dispersion uniformity of the ball asphalt in the castable system cannot be significantly improved. At this time, further extending the insulation time will also cause the volatilization and decomposition of some carbon oxides in the ball asphalt, which will not only fail to have a positive effect on the dispersion effect, but also increase unnecessary energy waste.
[0026] Furthermore, based on the mass of the castable raw material as a whole, a water reducer accounting for 0.15-0.25% of the mass of the castable raw material is added; the castable raw material and the water reducer are mixed according to the mass ratio and put into a high-powered mixer and stirred for 5-10 minutes to obtain a dry material mixture, and water accounting for 4.5-5wt.% of the dry material mixture is added, stirred in a high-powered mixer for 3-5 minutes, cast and molded, demolded after curing for 20-24 hours, and then subjected to a baking process.
[0027] Furthermore, the preparation method of the modified ball asphalt has the following specific steps: step 1: etching the ball asphalt and then drying it; step 2: immersing the ball asphalt prepared in step 1 in a nano-silica sol solution and drying it to obtain the modified ball asphalt. The surface of the unmodified ball asphalt is relatively smooth and has a low roughness. At this time, silicon dioxide cannot effectively coat it. After etching, the roughness of the ball asphalt can be improved, thereby improving the adhesion strength of nano-silicon dioxide on its surface.
[0028] Furthermore, the nano-silica sol solution used in step 2 is alkaline. Alkaline silica sol has a large specific surface area and a porous structure, and has good adsorption capacity.
[0029] Furthermore, the concentration of the nano-silica sol solution used in step 2 is 20-40wt.%; the mass ratio of the ball pitch to the nano-silica sol solution is 1:0.2-0.4. At the same time, according to theoretical calculations, the reaction ratio of carbon and silicon dioxide to form silicon carbide whiskers is 3:1. The molar ratio of the ball pitch with a rough surface to silicon dioxide is 1:0.2-0.4, at which time silicon dioxide and the carbon source can completely react to form silicon carbide whiskers, and the excess carbon source can provide a reducing environment for the reaction to promote the reaction, thereby making full use of the carbon source.
[0030] Furthermore, in step 1, the ball asphalt is etched, specifically, etching is performed using an acid solution.
[0031] Furthermore, the baking process also includes: heating from room temperature to 100°C at a heating rate of 15 to 20°C / h, and keeping at 100°C for 45 to 50 hours; heating from 100°C to 150°C at a heating rate of 15 to 20°C / h, and keeping at 150°C for 65 to 70 hours; heating from 150°C to between 330 and 370°C at a heating rate of 15 to 20°C / h; heating from 330 to 370°C to 550°C at a heating rate of 20 to 25°C / h, and keeping at 550°C for 65 to 70 hours; heating from 550°C to 800°C at a heating rate of 20 to 25°C / h, and keeping at 800°C for 55 to 60 hours.
[0032] It should be noted that the key point of the baking process in the present application is to keep the temperature at 330-370°C for a period of time so that the fluidity and microcrystallization degree of the ball pitch in the castable matrix can reach the best balance, and there are no excessive requirements for the baking system before and after the insulation at this temperature. The existing baking system can be directly adopted, but when the above-mentioned baking process is further adopted, it is beneficial to further ensure the performance of the resulting castable.
[0033] Furthermore, a method for preparing a castable for a blast furnace tapping channel using modified spherical pitch as a carbon source is characterized in that the microstructure of the castable prepared after a baking process contains a spider-web-like silicon carbide whisker structure.
[0034] Furthermore, the oxidation corrosion index of the castable obtained after the baking process is less than 17.9%.
[0035] In summary, the technical solution provided by the present invention can achieve the following beneficial effects compared with the prior art:
[0036] (1) The present invention modifies the ball asphalt and loads nano-silicon dioxide on its surface, thereby improving the hydrophilicity of the ball asphalt, improving the dispersibility of the ball asphalt in the castable matrix, and improving the anti-oxidation performance of the ball asphalt, thereby improving the residual carbon rate of the ball asphalt and making full use of the carbon source. At the same time, and more importantly, when the castable is subsequently baked, the nano-silicon dioxide loaded on the surface of the ball asphalt flows with it, and the uniformly dispersed nano-silicon dioxide can play a nucleation and filling effect, and by promoting the formation of mullite phase and silicon carbide whiskers, it can effectively improve the bonding between the ball asphalt and the matrix, improve the overall mechanical properties of the sample, and improve the densification degree of the sample.
[0037] (2) The present invention studies the low-temperature thermal behavior of ball pitch and optimizes the design of the baking system of the castable. By keeping it at 330-370°C for a period of time, the ball pitch can achieve an optimal balance between fluidity and microcrystallization in the castable matrix, achieve optimal flow expansion, and further promote the uniformity of dispersion of nano-silicon dioxide loaded on the surface of the ball pitch in the castable matrix, thereby improving the nucleation and filling effects of silicon dioxide.
[0038] (3) The present invention etches the pitch to make its surface rough, thereby improving the adhesion strength of nano-silicon dioxide on its surface. In addition, the experimental method of the modified pitch is simple, low-cost, and suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a SEM image of nano-silicon dioxide loaded on the surface of the ball asphalt in Example 1 of the present invention.
[0040] Figure 2 This is a SEM image of the internal microstructure of the castable sample prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0041] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with embodiments.
[0042] In the following embodiments, sodium tripolyphosphate is used as an example for the water reducer, which should not be construed as a limitation on the water reducer in the technical solution of the present invention. The water reducer can be any one of sodium tripolyphosphate, sodium hexametaphosphate, and polycarboxylic acid water reducers imported from BASF, Germany, or any combination of two or more thereof.
[0043] Example 1
[0044] This embodiment provides a method for preparing a high-performance blast furnace tapping ditch castable using modified spherical pitch as a carbon source, which is specifically as follows:
[0045] (I) Preparation of modified ball asphalt:
[0046] S1: Under room temperature, dry spherical asphalt with a particle size of 0 to 1 mm is immersed in an acid solution for natural reaction for 10 minutes, wherein the acid solution used is a 10wt.% dilute nitric acid solution. After the etching reaction is completed, it is dried at 60°C for 3 hours to obtain spherical asphalt with a rough surface.
[0047] S2: The rough-surfaced ball asphalt prepared in S1 is immersed in a 30wt.% nano-silica sol solution, and is naturally dried in a ventilated place to obtain a ball asphalt with nano-silica attached to the surface, and the modified ball asphalt maintains shape integrity; the nano-silica sol solution used is alkaline, and its pH value is 8; the mass of the rough-surfaced ball asphalt after etching and the mass of nano-silica contained in the nano-silica sol solution are 1:0.3.
[0048] The scanning electron microscope image of the prepared surface-loaded nano-silicon dioxide ball asphalt is as follows: Figure 1 shown.
[0049] (II) Preparation method of castable for blast furnace tapping channel
[0050] S1: Raw material preparation: The castable raw materials include 55wt.% brown corundum aggregate, 20wt.% silicon carbide, 15wt.% dense corundum compounded with α-alumina micropowder, 5wt.% calcium aluminate cement, 2wt.% metallic aluminum powder compounded with elemental silicon powder and 3wt.% modified spherical asphalt.
[0051] The particle size ratio of the brown corundum aggregate used is as follows: 5-8 mm accounts for 36wt.%, 3-5 mm accounts for 23wt.%, 1-3 mm accounts for 23wt.%, and 0.088-1 mm accounts for 18wt.%.
[0052] The particle size composition of the silicon carbide used is as follows: particles of 0.088-1 mm account for 45 wt.% of the silicon carbide, and particles smaller than 0.088 mm account for 55 wt.% of the silicon carbide.
[0053] The mass ratio of dense corundum to α-alumina micropowder in the dense corundum composite α-alumina micropowder used is 0.2. The dense corundum is a fine powder with a particle size less than 0.045 mm. The α-alumina micropowder has an Al2O3 content of ≥98wt.%, and its particle size distribution curve is a bimodal structure with bimodal peak values of 1.2μm and 2.3μm respectively.
[0054] The calcium aluminate cement used is Secar71 pure calcium aluminate cement.
[0055] The mass ratio of the metal aluminum powder to the elemental silicon powder in the metal aluminum powder compounded with the elemental silicon powder is 0.1.
[0056] S2: Based on the castable raw material described in S1 as a whole, a water reducing agent is added in an amount of 0.25% by mass of the castable raw material, wherein the water reducing agent used is sodium tripolyphosphate.
[0057] The above casting material raw materials and water reducing agent are stirred for 8 minutes to be fully mixed to obtain a dry material mixture; water accounting for 5% by mass of the dry material mixture is added; the mixture is stirred in a high-powered mixer for 4 minutes, cast into shape, and demoulded after curing for 20 hours.
[0058] S3: Baking is performed according to a baking curve, wherein the baking curve is as follows: a heating rate of 20°C / min from room temperature to 100°C, and a heat preservation period of 45 hours at 100°C; a heating rate of 20°C / min from 100°C to 150°C, and a heat preservation period of 65 hours at 150°C; a heating rate of 15°C / min from 150°C to 350°C, and a heat preservation period of 350°C; a heating rate of 20°C / h from 350°C to 550°C, and a heat preservation period of 550°C for 65 hours; a heating rate of 25°C / h from 550°C to 800°C, and a heat preservation period of 800°C for 55 hours.
[0059] The scanning electron microscope image of the sample of the blast furnace tapping channel castable prepared in this embodiment with modified spherical pitch as the carbon source after the initial high temperature service is as follows: Figure 2 As shown. Figure 2 It can be seen that a large number of spider-web-like silicon carbide whiskers can be observed in the matrix. The above sample was further tested, and the test results showed that the sample had a room temperature flexural strength of 11.7 MPa, a room temperature compressive strength of 53.2 MPa, an oxidation corrosion index of 15.7%, and a slag corrosion depth of 1.4 mm.
[0060] Example 2
[0061] This embodiment provides a method for preparing a high-performance blast furnace tapping ditch castable using modified spherical pitch as a carbon source, which is specifically as follows:
[0062] (I) Preparation of modified ball asphalt
[0063] S1: Under room temperature, dry spherical asphalt with a particle size of 0 to 1 mm is immersed in an acid solution for natural reaction for 10 minutes, wherein the acid solution used is a 10wt.% dilute nitric acid solution. After the etching reaction is completed, it is dried at 60°C for 3 hours to obtain spherical asphalt with a rough surface.
[0064] S2: The rough-surfaced ball asphalt obtained in S1 is immersed in a 40wt.% nano-silica sol solution, and is naturally dried in a ventilated place to obtain the ball asphalt with nano-silica attached to the surface; the nano-silica sol solution used is alkaline, and its pH value is 8; the mass of the ball asphalt after etching is 1:0.4 to the mass of the nano-silica contained in the nano-silica sol solution.
[0065] (II) Preparation method of castable for blast furnace tapping channel
[0066] S1: Raw material preparation: The castable raw materials include 50wt.% brown corundum aggregate, 23wt.% silicon carbide, 18wt.% dense corundum compounded with α-alumina micropowder, 5wt.% calcium aluminate cement, 1.5wt.% metallic aluminum powder compounded with elemental silicon powder and 2.5wt.% modified spherical asphalt.
[0067] The particle size ratio of the brown corundum aggregate used is as follows: 5-8 mm accounts for 45wt.%, 3-5 mm accounts for 15wt.%, 1-3 mm accounts for 30wt.%, and 0.088-1 mm accounts for 10wt.%.
[0068] The particle size composition of the silicon carbide used is as follows: particles of 0.088-1 mm account for 55 wt.% of the silicon carbide, and particles smaller than 0.088 mm account for 45 wt.% of the silicon carbide.
[0069] The mass ratio of dense corundum to α-alumina micropowder in the dense corundum composite α-alumina micropowder used is 0.1, the dense corundum is a fine powder with a particle size less than 0.045 mm, the α-alumina micropowder has an Al2O3 content of ≥98wt.%, and its particle size distribution curve is a bimodal structure, with bimodal peak values of 1.2μm and 2.3μm respectively.
[0070] The calcium aluminate cement used is Secar71 pure calcium aluminate cement.
[0071] The mass ratio of the metal aluminum powder to the elemental silicon powder in the metal aluminum powder compounded with the elemental silicon powder is 0.2.
[0072] S2: Based on the castable raw material described in S1 as a whole, a water reducing agent is added in an amount of 0.15% by mass of the castable raw material, wherein the water reducing agent used is sodium tripolyphosphate.
[0073] The above casting material raw materials and water reducing agent are stirred for 10 minutes to fully mix to obtain a dry material mixture; 4.5% of water by mass of the dry material mixture is added; the mixture is stirred in a high-powered mixer for 3 minutes, cast into shape, and demoulded after curing for 24 hours.
[0074] S3: Baking is performed according to a baking curve, wherein the baking curve is as follows: a heating rate of 20°C / min from room temperature to 100°C, and a heat preservation period of 50 h at 100°C; a heating rate of 20°C / min from 100°C to 150°C, and a heat preservation period of 70 h at 150°C; a heating rate of 15°C / min from 150°C to 350°C, and a heat preservation period of 350°C for 2.5 h; a heating rate of 20°C / h from 350°C to 550°C, and a heat preservation period of 550°C for 70 h; a heating rate of 25°C / h from 550°C to 800°C, and a heat preservation period of 60 h at 800°C.
[0075] After the first high-temperature service of the castable for blast furnace tapping channel prepared in this embodiment with modified spherical pitch as the carbon source, a large number of spider-web-like silicon carbide whiskers can be observed in the matrix using a scanning electron microscope. The above sample was further tested, and the test results showed that the room-temperature flexural strength of the sample was 11.4MPa, the room-temperature compressive strength was 51.5MPa, the oxidation corrosion index was 16.0%, and the slag corrosion depth was 1.4mm.
[0076] Example 3
[0077] This embodiment provides a method for preparing a high-performance blast furnace tapping ditch castable using modified spherical pitch as a carbon source, which is specifically as follows:
[0078] (I) Preparation of modified ball asphalt
[0079] S1: Under room temperature, dry spherical asphalt with a particle size of 0 to 1 mm is immersed in an acid solution for natural reaction for 10 minutes, wherein the acid solution used is a 10wt.% dilute nitric acid solution. After the etching reaction is completed, it is dried at 60°C for 3 hours to obtain spherical asphalt with a rough surface.
[0080] S2: The rough-surfaced ball asphalt obtained in S1 is immersed in a 20wt.% nano-silica sol solution, and is naturally dried in a ventilated place to obtain the ball asphalt with nano-silica attached to the surface; the nano-silica sol solution used is alkaline, and its pH value is 8; the mass ratio of the etched ball asphalt to the etched ball asphalt is 1:0.2.
[0081] (II) Preparation method of castable for blast furnace tapping channel
[0082] S1: Raw material preparation: The castable raw materials include 60wt.% brown corundum aggregate, 15wt.% silicon carbide, 16wt.% dense corundum compounded with α-alumina micropowder, 4wt.% calcium aluminate cement, 2wt.% metallic aluminum powder compounded with elemental silicon powder and 3wt.% modified ball asphalt.
[0083] The particle size ratio of the brown corundum aggregate used is as follows: 5-8 mm accounts for 25wt.%, 3-5 mm accounts for 35wt.%, 1-3 mm accounts for 15wt.%, and 0.088-1 mm accounts for 25wt.%.
[0084] The particle size composition of the silicon carbide used is as follows: the particle size of 0.088-1 mm accounts for 40 wt.% of the silicon carbide, and the particle size less than 0.088 mm accounts for 60 wt.% of the silicon carbide.
[0085] The mass ratio of dense corundum to α-alumina micropowder in the dense corundum composite α-alumina micropowder used is 0.15. The dense corundum is a fine powder with a particle size less than 0.045 mm. The α-alumina micropowder has an Al2O3 content of ≥98wt.%, and its particle size distribution curve is a bimodal structure with bimodal peak values of 1.2μm and 2.3μm respectively.
[0086] The calcium aluminate cement used is Secar71 pure calcium aluminate cement.
[0087] The mass ratio of the metal aluminum powder to the elemental silicon powder in the metal aluminum powder compounded with the elemental silicon powder is 0.15.
[0088] S2: Taking the castable raw material of S1 as a whole, a water reducing agent is added in an amount of 0.2% by mass of the castable raw material; wherein the water reducing agent used is sodium tripolyphosphate.
[0089] The above casting material raw materials and water reducing agent are stirred for 5 minutes to fully mix to obtain a dry material mixture; water accounting for 4.8% of the dry material mixture by mass is added; stirred in a high-powered mixer for 5 minutes, cast into shape, and demolded after curing for 22 hours.
[0090] S3: Baking is performed according to a baking curve, wherein the baking curve is as follows: a heating rate of 15°C / min from room temperature to 100°C, and a heat preservation period of 48 hours at 100°C; a heating rate of 15°C / min from 100°C to 150°C, and a heat preservation period of 68 hours at 150°C; a heating rate of 20°C / min from 150°C to 350°C, and a heat preservation period of 350°C for 4 hours; a heating rate of 25°C / h from 350°C to 550°C, and a heat preservation period of 550°C for 68 hours; a heating rate of 20°C / h from 550°C to 800°C, and a heat preservation period of 800°C for 58 hours.
[0091] The castable for blast furnace tapping channel prepared in this embodiment with modified spherical pitch as carbon source can observe spider web-like silicon carbide whiskers in the matrix using a scanning electron microscope after the initial high-temperature service. The test shows that the room-temperature flexural strength of the sample is 11.5MPa, the room-temperature compressive strength is 52.2MPa, the oxidation corrosion index is 16.5%, and the slag corrosion depth is 1.5mm.
[0092] Example 4
[0093] The present embodiment provides a method for preparing a high-performance blast furnace tapping ditch castable using modified spherical asphalt as a carbon source. The difference between the present embodiment 1 and the present embodiment 1 is that the raw material ratio of the blast furnace tapping ditch castable is different; specifically, the castable raw materials contain 57wt.% brown corundum aggregate, 20wt.% silicon carbide, 13wt.% dense corundum compounded with α-alumina micropowder, 6wt.% calcium aluminate cement, 1.5wt.% metallic aluminum powder compounded with elemental silicon powder and 2.5wt.% modified spherical asphalt.
[0094] And the baking process is different, specifically: the heating rate from room temperature to 100℃ is 18℃ / min, and the temperature is kept at 100℃ for 50 hours, the heating rate from 100℃ to 150℃ is 18℃ / min, and the temperature is kept at 150℃ for 70 hours, the heating rate from 150℃ to 350℃ is 18℃ / min, and the temperature is kept at 350℃ for 2.5 hours, the heating rate from 350℃ to 550℃ is 22℃ / h, and the temperature is kept at 550℃ for 65 hours, the heating rate from 550℃ to 800℃ is 22℃ / h, and the temperature is kept at 800℃ for 55 hours.
[0095] The castable for blast furnace tapping channel prepared in this embodiment with modified spherical pitch as carbon source can observe spider web-like silicon carbide whiskers in the matrix using a scanning electron microscope after the initial high-temperature service. After testing: the room-temperature flexural strength of the sample is 11MPa, the room-temperature compressive strength is 52.7MPa, the oxidation corrosion index is 15.9%, and the slag corrosion depth is 1.4m.
[0096] Example 5
[0097] The present embodiment provides a method for preparing a high-performance blast furnace iron tapping ditch castable with modified spherical pitch as a carbon source. The difference between the present embodiment 1 is that the baking process is different, specifically: the heating rate from room temperature to 100°C is 20°C / min, and the temperature is kept at 100°C for 45 hours, the heating rate from 100°C to 150°C is 20°C / min, and the temperature is kept at 150°C for 65 hours, the heating rate from 150°C to 330°C is 15°C / min, and the temperature is kept at 330°C for 4 hours, the heating rate from 330°C to 550°C is 20°C / h, and the temperature is kept at 550°C for 65 hours, the heating rate from 550°C to 800°C is 25°C / h, and the temperature is kept at 800°C for 55 hours.
[0098] The castable for blast furnace tapping channel prepared in this embodiment with modified spherical pitch as carbon source can observe spider web-like silicon carbide whiskers in the matrix using a scanning electron microscope after the initial high-temperature service. After testing: the room-temperature flexural strength of the sample is 10.5MPa, the room-temperature compressive strength is 47.8MPa, the oxidation corrosion index is 17.9%, and the slag corrosion depth is 1.7mm.
[0099] Example 6
[0100] The present embodiment provides a method for preparing a high-performance blast furnace iron tapping ditch castable with modified spherical pitch as a carbon source. The difference between the present embodiment 1 is that the baking process is different, specifically: the heating rate from room temperature to 100°C is 20°C / min, and the temperature is kept at 100°C for 45 hours, the heating rate from 100°C to 150°C is 20°C / min, and the temperature is kept at 150°C for 65 hours, the heating rate from 150°C to 340°C is 15°C / min, and the temperature is kept at 340°C for 3 hours, the heating rate from 340°C to 550°C is 20°C / h, and the temperature is kept at 550°C for 65 hours, the heating rate from 550°C to 800°C is 25°C / h, and the temperature is kept at 800°C for 55 hours.
[0101] The castable for blast furnace tapping channel prepared in this embodiment with modified spherical pitch as carbon source can observe spider web-like silicon carbide whiskers in the matrix using a scanning electron microscope after the initial high-temperature service. After testing: the room-temperature flexural strength of the sample is 11.3MPa, the room-temperature compressive strength is 49.3MPa, the oxidation corrosion index is 16.8%, and the slag corrosion depth is 1.5mm.
[0102] Example 7
[0103] The present embodiment provides a method for preparing a high-performance blast furnace iron tapping ditch castable with modified spherical pitch as a carbon source. The difference between the present embodiment 1 is that the baking process is different, specifically: the heating rate from room temperature to 100°C is 20°C / min, and the temperature is kept at 100°C for 45 hours, the heating rate from 100°C to 150°C is 20°C / min, and the temperature is kept at 150°C for 65 hours, the heating rate from 150°C to 360°C is 15°C / min, and the temperature is kept at 360°C for 2.5 hours, the heating rate from 360°C to 550°C is 20°C / h, and the temperature is kept at 550°C for 65 hours, the heating rate from 550°C to 800°C is 22°C / h, and the temperature is kept at 800°C for 55 hours.
[0104] The castable for blast furnace tapping channel prepared in this embodiment with modified spherical pitch as carbon source can observe spider web-like silicon carbide whiskers in the matrix using a scanning electron microscope after the initial high-temperature service. After testing: the room-temperature flexural strength of the sample is 11.5MPa, the room-temperature compressive strength is 52.5MPa, the oxidation corrosion index is 16.4%, and the slag corrosion depth is 1.5mm.
[0105] Example 8
[0106] The present embodiment provides a method for preparing a high-performance blast furnace iron tapping ditch castable with modified spherical pitch as a carbon source. The difference between the present embodiment 1 is that the baking process is different, specifically: the heating rate from room temperature to 100°C is 20°C / min, and the temperature is kept at 100°C for 45 hours, the heating rate from 100°C to 150°C is 20°C / min, and the temperature is kept at 150°C for 65 hours, the heating rate from 150°C to 370°C is 15°C / min, and the temperature is kept at 370°C for 2 hours, the heating rate from 370°C to 550°C is 20°C / h, and the temperature is kept at 550°C for 65 hours, the heating rate from 550°C to 800°C is 25°C / h, and the temperature is kept at 800°C for 55 hours.
[0107] The castable for blast furnace tapping channel prepared in this embodiment with modified spherical pitch as carbon source can observe spider web-like silicon carbide whiskers in the matrix using a scanning electron microscope after the initial high-temperature service. After testing: the room-temperature flexural strength of the sample is 11.0MPa, the room-temperature compressive strength is 48.3MPa, the oxidation corrosion index is 17.2%, and the slag corrosion depth is 1.6mm.
[0108] Comparative Example 1
[0109] The comparative example provides a method for preparing a high-performance blast furnace iron tapping ditch castable with modified spherical pitch as a carbon source, which differs from the present embodiment 1 in that the baking process is different; specifically, the heating rate from room temperature to 100°C is 20°C / min, and the temperature is kept at 100°C for 45 hours; the heating rate from 100°C to 150°C is 20°C / min, and the temperature is kept at 150°C for 65 hours; the heating rate from 150°C to 300°C is 15°C / min, and the temperature is kept at 300°C for 3 hours; the heating rate from 300°C to 550°C is 20°C / h, and the temperature is kept at 550°C for 65 hours; the heating rate from 550°C to 800°C is 25°C / h, and the temperature is kept at 800°C for 55 hours.
[0110] The high-performance blast furnace tapping ditch castable prepared in this comparative example with modified spherical pitch as the carbon source was subjected to the first high-temperature service. A small amount of silicon carbide whiskers can be observed in the matrix using a scanning electron microscope. The above sample was further tested. After testing: the room-temperature flexural strength of the castable sample was 9.3MPa, the room-temperature compressive strength was 41.6MPa, the oxidation corrosion index was 20.2%, and the slag corrosion depth was 2.3mm.
[0111] Comparative Example 2
[0112] The comparative example provides a method for preparing a high-performance blast furnace iron tapping ditch castable with modified spherical pitch as a carbon source. The difference between the comparative example and the embodiment 1 is that the baking curve is different, specifically: the heating rate from room temperature to 100°C is 20°C / min, and the temperature is kept at 100°C for 45 hours; the heating rate from 100°C to 150°C is 20°C / min, and the temperature is kept at 150°C for 65 hours; the heating rate from 150°C to 320°C is 15°C / min, and the temperature is kept at 320°C for 3 hours; the heating rate from 330°C to 550°C is 20°C / h, and the temperature is kept at 550°C for 65 hours; the heating rate from 550°C to 800°C is 25°C / h, and the temperature is kept at 800°C for 55 hours.
[0113] The high-performance blast furnace tapping ditch castable prepared in this comparative example with modified spherical pitch as the carbon source was subjected to the first high-temperature service. A small amount of silicon carbide whiskers can be observed in the matrix using a scanning electron microscope. The above sample was further tested, and the test results showed that the room-temperature flexural strength of the sample was 10.2MPa, the room-temperature compressive strength was 44.8MPa, the oxidation corrosion index was 18%, and the slag corrosion depth was 2mm.
[0114] Comparative Example 3
[0115] The comparative example provides a method for preparing a high-performance blast furnace iron tapping ditch castable with modified spherical pitch as a carbon source. The difference between the comparative example and the embodiment 1 is that the baking curve is different, specifically: the heating rate from room temperature to 100°C is 20°C / min, and the temperature is kept at 100°C for 45 hours; the heating rate from 100°C to 150°C is 20°C / min, and the temperature is kept at 150°C for 65 hours; the heating rate from 150°C to 380°C is 15°C / min, and the temperature is kept at 380°C for 3 hours; the heating rate from 320°C to 550°C is 20°C / h, and the temperature is kept at 550°C for 65 hours; the heating rate from 550°C to 800°C is 25°C / h, and the temperature is kept at 800°C for 55 hours.
[0116] The high-performance blast furnace tapping ditch castable prepared in this comparative example with modified spherical pitch as the carbon source can observe silicon carbide whiskers in the matrix using a scanning electron microscope after the initial high-temperature service. The above sample was further tested, and the test results showed that the room-temperature flexural strength of the sample was 10.3MPa, the room-temperature compressive strength was 45.6MPa, the oxidation corrosion index was 18.2%, and the slag corrosion depth was 1.9mm.
[0117] Comparative Example 4
[0118] The present comparative example provides a method for preparing a high-performance blast furnace iron tapping ditch castable with modified spherical pitch as a carbon source. The difference between the comparative example and the present embodiment 1 is that the baking curve is different, specifically: the heating rate from room temperature to 100°C is 20°C / min, and the temperature is kept at 100°C for 45 hours; the heating rate from 100°C to 150°C is 20°C / min, and the temperature is kept at 150°C for 65 hours; the heating rate from 150°C to 400°C is 15°C / min, and the temperature is kept at 400°C for 3 hours; the heating rate from 400°C to 550°C is 20°C / h, and the temperature is kept at 550°C for 65 hours; the heating rate from 550°C to 800°C is 25°C / h, and the temperature is kept at 800°C for 55 hours.
[0119] The high-performance blast furnace tapping channel castable prepared in this comparative example with modified spherical pitch as the carbon source can observe silicon carbide whiskers in the matrix using a scanning electron microscope after the initial high-temperature service. The above sample was further tested, and the test results showed that the room-temperature flexural strength of the sample was 9.8MPa, the room-temperature compressive strength was 45.6MPa, the oxidation corrosion index was 21.2%, and the slag corrosion depth was 2.3mm.
[0120] Comparative Example 5
[0121] The comparative example provides a method for preparing a high-performance blast furnace iron tapping ditch castable with modified spherical pitch as a carbon source. The difference between the comparative example and the embodiment 1 is that the baking curve is different, specifically: the heating rate from room temperature to 100°C is 20°C / min, and the temperature is kept at 100°C for 45 hours; the heating rate from 100°C to 150°C is 20°C / min, and the temperature is kept at 150°C for 65 hours; the heating rate from 150°C to 450°C is 15°C / min, and the temperature is kept at 450°C for 3 hours; the heating rate from 450°C to 550°C is 20°C / h, and the temperature is kept at 550°C for 65 hours; the heating rate from 550°C to 800°C is 25°C / h, and the temperature is kept at 800°C for 55 hours.
[0122] The high-performance blast furnace tapping channel castable prepared in this comparative example with modified spherical pitch as the carbon source can observe silicon carbide whiskers in the matrix using a scanning electron microscope after high-temperature service. The above sample was further tested, and the test results showed that the room-temperature flexural strength of the sample was 6.8MPa, the room-temperature compressive strength was 35.0MPa, the oxidation corrosion index was 30.5%, and the slag corrosion depth was 2.7mm.
[0123] Comparative Example 6
[0124] This comparative example provides a method for preparing a high-performance blast furnace iron ditch castable using modified spherical pitch as a carbon source. The difference between this method and Example 1 is that the mass proportion of brown corundum aggregate in the castable raw material is 54%, and 1wt.% of nano-silicon dioxide is added, and the rest of the operations are basically the same.
[0125] The sample of the castable for blast furnace tapping channel prepared in this comparative example with modified spherical pitch as carbon source after high temperature service can be observed with silicon carbide whiskers in the matrix using a scanning electron microscope. The above sample is further tested, and the test results show that the sample has a room temperature flexural strength of 9.6MPa, a room temperature compressive strength of 43.8MPa, an oxidation corrosion index of 23.7%, and a slag corrosion depth of 2.4mm.
Claims
1. A castable for a blast furnace tapping channel using modified spherical pitch as a carbon source, characterized in that: The castable material adopts Al2O3-SiC-C castable material, and its raw material contains 2.3-5wt.% modified ball asphalt; the modified ball asphalt is ball asphalt with nano silicon dioxide loaded on the surface.
2. The castable for blast furnace tapping channel using modified spherical pitch as carbon source according to claim 1, characterized in that: The particle size of the ball asphalt is 0-1 mm.
3. The castable for blast furnace tapping channel using modified spherical pitch as carbon source according to claim 1, characterized in that: The castable raw material also contains 50-60wt.% of brown corundum aggregate, 15-23wt.% of silicon carbide, 11-38wt.% of dense corundum compounded with α-alumina micropowder, 4-6wt.% of calcium aluminate cement, and 1.5-2.0wt.% of metal aluminum powder compounded with elemental silicon powder.
4. The castable for blast furnace tapping channel using modified spherical pitch as carbon source according to claim 3, characterized in that: The particle size distribution of the brown corundum aggregate is as follows: 5-8 mm particles account for 25-45 wt.% of the brown corundum aggregate, 3-5 mm particles account for 15-35 wt.% of the brown corundum aggregate, 1-3 mm particles account for 15-30 wt.% of the brown corundum aggregate, and 0.088-1 mm particles account for 10-25 wt.% of the brown corundum aggregate; And / or the particle size composition of the silicon carbide is: 0.088-1 mm accounts for 40-55 wt.% of the silicon carbide, and less than 0.088 mm accounts for 45-60 wt.% of the silicon carbide; And / or the mass ratio of dense corundum to α-alumina micropowder in the dense corundum-α-alumina micropowder is 0.1-0.2, and the particle size of the dense corundum is less than 0.045 mm; the α-alumina micropowder is selected from α-alumina micropowder with an Al2O3 content of ≥98wt.%, and a particle size distribution curve of a bimodal structure, with bimodal peak values of 1.2μm and 2.3μm respectively; And / or the mass ratio of the metal aluminum powder to the elemental silicon powder in the metal aluminum powder compounded with the elemental silicon powder is 0.1 to 0.2; And / or the calcium aluminate cement is Secar71 pure calcium aluminate cement; And / or the water reducer is one or more of sodium tripolyphosphate, sodium hexametaphosphate, and polycarboxylic acid water reducer imported from BASF of Germany.
5. The method for preparing a high-performance blast furnace tapping ditch castable using modified spherical pitch as a carbon source according to any one of claims 1 to 4, characterized in that: The method comprises a baking process, which comprises: keeping the castable at 330-370°C for 2.5-4 hours.
6. The method for preparing a high-performance blast furnace tapping ditch castable using modified spherical pitch as a carbon source according to claim 5, characterized in that: include: Based on the mass of the castable raw material as a whole, a water reducer accounting for 0.15-0.25% of the mass of the castable raw material is added; the castable raw material and the water reducer are mixed according to the mass ratio and put into a high-powered mixer and stirred for 5-10 minutes to obtain a dry material mixture, and water accounting for 4.5-5wt.% of the dry material mixture is added, stirred in a high-powered mixer for 3-5 minutes, cast and molded, demolded after curing for 20-24 hours, and then baked.
7. The method for preparing a castable for a blast furnace tapping channel using modified spherical pitch as a carbon source according to claim 5, characterized in that: The preparation method of the modified ball asphalt comprises the following specific steps: Step 1: Etch the ball asphalt and then dry it; Step 2: Immerse the ball pitch prepared in step 1 in a nano-silica sol solution, and obtain modified ball pitch after drying.
8. The method for preparing a castable for a blast furnace tapping channel using modified spherical pitch as a carbon source according to claim 7, characterized in that: The nano-silica sol solution used in step 2 is alkaline; And / or the concentration of the nano-silica sol solution in step 2 is 20-40wt.%, and the molar ratio of the ball pitch used to the nano-silica contained in the nano-silica sol solution is 1:0.2-0.4; And / or in the step 1, the ball pitch is etched, specifically, etching is performed using an acid solution.
9. The method for preparing a high-performance blast furnace tapping ditch castable using modified spherical pitch as a carbon source according to any one of claims 5 to 8, characterized in that: The baking process also includes: heating from room temperature to 100°C at a heating rate of 15 to 20°C / h, and keeping at 100°C for 45 to 50 hours; heating from 100°C to 150°C at a heating rate of 15 to 20°C / h, and keeping at 150°C for 65 to 70 hours; heating from 150°C to between 330 and 370°C at a heating rate of 15 to 20°C / h; heating from 330 to 370°C to 550°C at a heating rate of 20 to 25°C / h, and keeping at 550°C for 65 to 70 hours; heating from 550°C to 800°C at a heating rate of 20 to 25°C / h, and keeping at 800°C for 55 to 60 hours.
10. The method for preparing a castable for a blast furnace tapping channel using modified spherical pitch as a carbon source according to any one of claims 5 to 8, characterized in that: The microstructure of the castable prepared after the baking process contains a spider web-like silicon carbide whisker structure; And / or the oxidation corrosion index of the castable obtained after the baking process is less than 17.9%.
Citation Information
Patent Citations
Castable for blast-furnace tapping channel and preparation method thereof
CN103664211A
Iron runner casting material for blast furnaces and preparation method thereof
CN109336622A
High-oxidation-resistance non-cement bonded Al2O3-SiC-C refractory castable and preparation method thereof
CN112608138A
Thermal insulation
GB1444577A
Cassette for substrate
JP2002080720A